Memahami Adopsi Mobile Banking di Kalangan UMKM di Kota Batu: Mengintegrasikan Model Penerimaan Teknologi dan Keunggulan Relatif - Prayogi Restia Saputra; Andriati Aziizah Syafitri (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2026)
This study investigates the factors influencing SMEs’ intention to adopt mobile banking by integrating the Technology Acceptance Model (TAM) and Diffusion of Innovation Theory (DOI). Specifically, the study examines the effects of Perceived Ease of Use (PEOU), Perceived Usefulness (PU), and Relative Advantage (RA) on Behavioral Intention (BI) to use mobile banking services. A quantitative research approach was employed using a survey of SME owners and managers in Batu City, Indonesia. Data were collected from 165 respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The findings reveal that all proposed relationships are significant. Perceived Ease of Use positively influences both Perceived Usefulness and Behavioral Intention. Perceived Usefulness significantly affects Behavioral Intention and emerges as one of the strongest predictors of mobile banking adoption. Furthermore, Relative Advantage significantly influences both Perceived Usefulness and Behavioral Intention, indicating that SME owners are more likely to adopt mobile banking when they perceive clear advantages over conventional banking methods. This study contributes to the literature by extending TAM through the integration of Relative Advantage from Diffusion of Innovation Theory. The findings provide valuable insights for banking institutions and policymakers seeking to promote digital financial inclusion and accelerate the adoption of mobile banking among SMEs.